Mechanical properties and biological durability in soil contact of chemically modified wood treated in an open or in a closed system using glycerol/maleic anhydride systems. Issue 5 (3rd September 2022) - Mubarok, Mahdi; Militz, Holger; Dumarcay, Stéphane; Darmawan, Wayan; Hadi, Yusuf Sudo; Gérardin, Philippe
ABSTRACT: This paper presents mechanical properties and biological durability properties against soft-rot (soil bed test) and subterranean termites (grave-yard test) of the wood modified with a vinylic derivative of glycerol or polyglycerol and maleic anhydride at different curing conditions. Wood modification was performed through impregnation of European beech ( Fagus sylvatica ) with an aqueous solution of polyglycerol maleate, glycerol maleate, or maleic anhydride at 10 or 20% w/w concentration, followed with curing under oven heating (OHT) in an open system (120°C, 150°C, or 220°C) or under heat pressurised steam (HPS) at 150°C in a closed system. Results revealed that almost all modified wood presented higher modulus of elasticity (MOE) values than untreated wood, however, modulus of rupture (MOR) and work to maximum load in bending (WMLB) decreased considerably. Biological durability in the soil bed test against soft-rot indicated that almost all modified wood was specified as "durable" to "very durable". However, among the treatments, the wood modified with polyglycerol maleate/glycerol maleate/maleic anhydride at 20% under OHT 150°C or the wood modified at lower additive concentration (10%) under OHT 220°C presented excellent durability against subterranean termites within a period of 328 days in the field.